AB1037 SEROLOGICAL PHENOTYPES, UVEITIS AND DISEASE ACTIVITY INTO ADULTHOOD: LONG TERM OUTCOME IN A COHORT OF PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITIS. (June 2019) - Priora, Marta; Manetta, Tilde; Parisi, Simone; Chiara Ditto, Maria; Sanna, Silvia; Borrelli, Richard; Fusaro, Enrico
Abstract : Background: Deepening the long-term study in adulthood of Juvenile Idiopathic Arthritis (JIA) is fundamental in order to expand knowledge of the pathogenesis, optimize the therapeutic choices, favour a more active communication between paediatric and adult care specialists. Objectives: The present project deals with adult patients affected by JIA. The main objectives were those of: analyse the serological profile (rheumatoid factor RF- IgM, ACPA IgG, ANA) of such patients to investigate possible seroconversions in adulthood compared to the diagnosis in paediatric age; investigate whether correlations between antibodies (Ab) and diagnostic subgroups subsist in adulthood; evaluate the association between Ab and disease activity; investigate the association between the presence of uveitis in the medical history and specific Ab, diagnostic subgroups and disease activity. Methods: 68 patients were selected. Data were collected from medical records, a sample was taken to search for ANA, RF and ACPA; clinical data were collected on the evaluation of disease activity, using JADAS27 and SDAI as clinical scores (fig.1 ) Results: The data obtained were significant for the negativization of ANA in adulthood: at the diagnosis 45.6% of patients had ANA positivity, while in adulthood 13.2%. The difference was statistically significant. The Ab picture of both RF and ACPA remains unchanged in adulthood, therefore there was neither a significant positivization nor negativization. The concomitant positivity for RF and ACPA was found to exist, demonstrating statistical significance for both the diagnosis and the adulthood (p <0.05). To further confirm their classifying role, RF and ACPA were correlated with the polyarticular subgroup in childhood and adulthood (p <0.05), while ANA (both at diagnosis and in adulthood) did not correlate with any diagnostic subgroup (p> 0.05). A higher incidence of uveitis was not correlated either with the presence of ANA in paediatric age, nor in adulthood, but is instead associated with the diagnosis of oligoarticular JIA (p = 0.002). Analyses of the positivity for RF and ACPA (in relation to disease activity calculated with clinimetric indices such as JADAS27, SDAI and CDAI) detected the negative prognostic role of the two Ab as they correlated with higher disease activity in the population of the patients in the study (fig.2 ) Conclusion: In a rheumatological scenario enriched of great improvements in the diagnostic and therapeutic field during the last decades, a far from negligible portion of patients with JIA requires the continuation of rheumatological care in adulthood. The analyses of the present study report a significant negativization of ANA, thus suggesting the need to confirm the presence of these Ab in adulthood, and the difficulty in recognizing the classifying role of such Ab. The serological profile of RF and ACPA remains unchanged in adulthood, their correlation with the polyarticular subgroup is maintained even in the long term and both correlate with greater disease activity in adulthood. References: [1] Oliveira-Ramos F, Eusbio M, et al. Juvenile idiopathic arthritis in adulthood: fulfilment of classification criteria for adult rheumatic diseases, long-term outcomes and predictors of inactive disease, functional status and damage. RMD Open.2016; (2) [2] Coulson EJ, Hanson HJM, et al. What does an adult rheumatologist need to know about juvenile idiopathic arthritis? Rheumatology. 2014;53(12). [3] Selvaag AM, Aulie HA, et al. Disease progression into adulthood and predictors of long-term active disease in juvenile idiopathic arthritis. Ann Rheum Dis. 2016;75(1)Figure 1 Disclosure of Interests: Marta Priora Grant/research support from: Sanofi SpA, Tilde Manetta: None declared, Simone Parisi Speakers bureau: Chiesi, Jansenn, Pfizer, Celgene, Abbvie, Lilly., Maria Chiara Ditto: None declared, Silvia Sanna Grant/research support from: Novartis, Richard Borrelli: None declared, Enrico Fusaro Grant/research support from: Abbvie Abiogen Actelion Amgen Biogen BMS Celgene Grunenthal GSK Janssen Lilly MSD Mundipharma Novartis Pfizer Roche SANOFI SOBI UCB